2011
DOI: 10.1136/bjsports-2011-090337
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual cues in the regulation of exercise performance – physical sensations of exercise and awareness of effort interact as separate cues

Abstract: It has been argued that the physical sensations induced by exercise, measured as the ratings of perceived exertion (RPE), are distinct from the sense of effort. This study aimed to determine whether a new measure of task effort -the Task Effort and Awareness (TEA) score -is able to measure sensations distinct from those included in the conventional RPE scale. Seven well-trained cyclists completed a maximal effort 100 km time trial (TT) and a submaximal trial at 70% of the power sustained during the TT (70% TT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 32 publications
(32 reference statements)
2
89
2
1
Order By: Relevance
“…A high score means homeostatic disturbance, facing the choice of reducing intensity or not finishing. Swart and colleagues [20] proposed that physical sensations of effort act as the template regulating performance during exercise and that deviation from that template produces an increase in the sense of mental effort. The latter was measured with Task Effort and Awareness score (TEA-score).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A high score means homeostatic disturbance, facing the choice of reducing intensity or not finishing. Swart and colleagues [20] proposed that physical sensations of effort act as the template regulating performance during exercise and that deviation from that template produces an increase in the sense of mental effort. The latter was measured with Task Effort and Awareness score (TEA-score).…”
Section: Discussionmentioning
confidence: 99%
“…The latter was measured with Task Effort and Awareness score (TEA-score). It was concluded that the conscious decision of whether to maintain or change the current workload could be the outcome of a balance between motivation, affect, and sense of mental effort [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly Hutchinson & Tenenbaum (2006) have argued that it is an oversimplification of the psychophysiological construct to base perceived exertion on a physiological index, and that a single-item measure of effort is insufficient to capture the wide range of sensations experienced during the course of an exercise bout. Both Hampton et al (2001) and Swart et al (2012) have also suggested that the sense of effort is a subjective sensation, and recently it has been proposed that the generation of the sense of effort is independent of afferent physiological feedback (Smirmaul, 2012). This suggestion is in congruence with the findings of this study whereby absolute work rates did not differ despite differences in peripheral physiological status.…”
Section: Volume 8 | Issue 3| 2013 | 826mentioning
confidence: 99%